Sultanic Titles in the Fatimid State and Their Religious and Political Significance in Morocco from the Year 296362 AH / 908 972 AD - Nada Abbas Farhan Musa Al-Shammari; A. L. Shatha Galeb Hassan; A. L. Asma Razzaq Shinawa (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The Ismaili sect successfully maintained its survival over centuries and played pivotal roles in Islamic political history. Specific Background During the establishment of the Fatimid state in Morocco between 908 and 972 AD, hidden imams and prominent preachers utilized various aliases to protect their identities from persecution. Knowledge Gap Previous historical literature has not comprehensively collected or analyzed these dispersed religious and political appellations in a singular scholarly study. Aims This study investigates the theological and political significance of the designations adopted by Ismaili hidden imams, preachers, and caliphs. Results The findings reveal that hidden imams used multiple pseudonyms for concealment, while prominent preachers in Yemen and Morocco adopted distinct monikers to propagate the doctrine safely. Furthermore, caliphs deliberately assumed grand designations and utilized inscribed rings featuring pious phrases to openly compete with rival leaders and symbolize their supreme domination. Novelty This research aggregates scattered historical translations to provide a unified framework for understanding Ismaili terminology. Implications Comprehending these appellations provides profound insights into internal state structures, demonstrating how royal titles served as a crucial instrument for ideological legitimization. Highlights: Hidden imams utilized multiple pseudonyms to avoid capture during secret doctrinal propagation. Prominent preachers spreading Ismaili beliefs adopted specific aliases to recruit regional supporters safely. Caliphs engraved ideological phrases on royal rings to assert territorial domination. Keywords: Ismaili Doctrine, Hidden Imams, Religious Appellations, Ideological Legitimization, Fatimid Caliphs